Science Terminology for Grade IV Elementary School in SIBI to Realize Inclusive Learning for Deaf Students - Puspita Sari, Ni Kadek Gina; Putu Nanci Riastini; Dewa Gede Firstia Wirabrata (Universitas Pendidikan Ganesha, 2025)
Problems occur in learning for deaf that not inclusive because lot of science terminology that not available in SIBI. The research aims to investigate Grade Four Elementary School science terminology found in SIBI and investigate number of Grade four Elementary School science terminology found in SIBI. Method used is mixed exploratory methods. Data collection techniques carried out qualitatively through document studies, interviews and observations and quantitatively through checklist sheets. The qualitative data analysis technique uses Miles and Huberman's theory, while quantitative data is carried out using percentage formula. In SIBI there is general terminology such as